Analisis Yuridis Terhadap Implementasi Jaminan Kesehatan Nasional (JKN) dalam Perspektif Hukum Kesehatan di Indonesia - Adi Arianto (Jurnal JURISTIC, 2025)
Indonesia's healthcare system underwent a significant transformation with the launch of the National Health Insurance Program (JKN) in 2014. JKN aims to ensure equitable access to healthcare for all citizens, in accordance with the principles of social justice and the right to health. While the program offers a solution to address disparities in healthcare services, its implementation faces challenges, such as limited health facilities, delays in claim payments, and perceived lower quality of care for JKN participants. These issues raise questions about the effectiveness of existing regulations and their impact on equity in access to health services. This study uses a normative juridical approach to analyse regulations and provide recommendations for improvements in JKN implementation. By understanding the existing legal and administrative constraints, it is hoped that JKN can function more optimally in realizing the health welfare of the Indonesian people.